Relationship between anxiety and overactive bladder syndrome in older women - Aline Teixeira Alves; Raquel Henriques Jácomo; Liana Barbaresco Gomide; Patrícia Azevedo Garcia; Albênica Paulino dos Santos Bontempo; Margô Gomes de Oliveira Karnikoskwi (Federação Brasileira das Sociedades de Ginecologia e Obstetrícia, 2014)
PURPOSE: The objective of this study was to investigate the relationship between overactive bladder syndrome and anxiety in older women. METHODS: Of the 198 older women who were invited, 29 were excluded and 166 were then divided into two groups according to the Advanced Questionnaire of Overactive Bladder (OAB-V8): one group with overactive bladder symptoms (OAB-V8≥8) and the other without the symptoms of an overactive bladder (OAB-V8<8). The purpose was to conduct a frequency analysis and to investigate the relation of the social demographic data and anxiety in the two groups. The Beck Anxiety Inventory (BAI) was used to evaluate the level of anxiety. The Kolmogorov-Smirnov test was used to determine the distribution of the data. The differences between the two groups for the continuous variables were analyzed by the Mann-Whitney U test, the differences for the categorical variables were analyzed by the Chi-Square test and the association between the continuous variables was analyzed by the Spearman Correlation test. The tests were two-tailed with a confidence level of 5%. RESULTS: Overall, the frequency of an overactive bladder was present in 117 (70.5%) of the participants. The body mass index (BMI) of the group with overactive bladder symptoms was significantly higher than the BMI of those without these symptoms (p=0.001). A higher prevalence of mild, moderate and severe anxiety was observed among older women with overactive bladder symptoms. In addition, the overactive bladder symptoms group presented a positive low correlation with anxiety symptoms (r=0.345) and with BMI (r=0.281). There was a small correlation between BMI and anxiety symptoms (r=0.164). CONCLUSIONS: Overactive bladder syndrome was prevalent among older women and the existence of these symptoms was linked to the presence of mild, moderate and/or severe anxiety symptoms.